The Effectiveness of TPR (Total Physical Response) Method in English Vocabulary Mastery of Elementary School Children - Ice Sariyati (Master Program in Linguistics, Diponegoro University, 2013)
This research employed a mixed method, combining quantitative and qualitative methods. To achieve the aims of the study, quasi-experimental design was used, involving two groups (control and experiment) at the first grade in one Islamic elementary school in Bandung and employing pretest, treatment (TPR method to experiment group, conventional method to control group) and posttest. The result of control class score computation to compare pretest score with posttest score showed that there is no significant difference between the pre-test and post-test score of control class. On the contrary, the result of experiment class score computation to compare pretest score with posttest score showed that there was significant difference between the pretest and posttest score of experiment class. Therefore, it can be concluded that the vocabulary mastery of experiment group was significantly improved. Penelitian ini menggunakan sebuah metode gabung, yang menggabungkan metode kuantitatif dan kualitatif. Untuk mencapai tujuan penelitian ini, desain quasi-eksperimental digunakan dengan melibatkan dua kelompok (kendali dan eksperimental) di kelas satu sekolah dasar Islam di Bandung dan menggunakan pretes, perlakuan (metode TPR untuk kelompok eksperimental, metode konvensional untuk kelompok kendali) dan postes. Hasil perhitungan nilai kelas kendali dengan membandingkan nilai pretes dan postes menunjukkan bahwa tidak ada perbedaan yang signifikan antara nilai pretes dan postes di kelas kendali. Sebaliknya, hasil perhitungan nilai kelas eksperimental dengan membandingkan nilai pretes dan postes menunjukkan bahwa terdapat perbedaan yang signifikan antara nilai pretes dan nilai postes di kelompok eksperimental. Oleh karena itu, dapat disimpulkan bahwa penguasaan kosakata dikelas eksperimental dapat meningkat secara signifikan.